2020
DOI: 10.1016/j.metop.2020.100052
|View full text |Cite
|
Sign up to set email alerts
|

Renin-Angiotensin System overactivation in polycystic ovary syndrome, a risk for SARS-CoV-2 infection?

Abstract: Background The SARS-CoV-2 coronavirus gains entry to target cells via the angiotensin-converting enzyme 2 (ACE2) receptor present on cells in blood vessels, lungs, heart, intestines, and kidneys. Renin-Angiotensin System (RAS) overactivity has also been described in metabolic syndrome, type 2 diabetes (T2D) and obesity, conditions shared by women with polycystic ovary syndrome (PCOS) We hypothesized that RAS overactivity may be present in PCOS. Methods We determined pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 43 publications
2
35
1
Order By: Relevance
“…These protein panels target biological processes involved in vessel damage, platelet degranulation, the coagulation cascade and the acute phase response [ 1 ], with greater protein changes dependent on the COVID-19 severity. However, it is observed that in metabolic conditions such as polycystic ovary syndrome expressed proteins differ compared to control women [ 2 ] and PCOS patients have increased platelet aggregation and decreased plasma fibrinolytic activity, resulting in a prothrombotic propensity [ 3 , 4 ], with elevated coagulation markers [ 5 ]. Therefore, any biomarkers reflecting COVID-19 disease and its severity would necessarily have to be independent of differentially-expressed proteins relating to other conditions; therefore, this proteomic analysis was undertaken in women with and without PCOS to compare with the proteomic biomarkers recently described in COVID-19 using shotgun proteomics followed by parallel reaction monitoring [ 1 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These protein panels target biological processes involved in vessel damage, platelet degranulation, the coagulation cascade and the acute phase response [ 1 ], with greater protein changes dependent on the COVID-19 severity. However, it is observed that in metabolic conditions such as polycystic ovary syndrome expressed proteins differ compared to control women [ 2 ] and PCOS patients have increased platelet aggregation and decreased plasma fibrinolytic activity, resulting in a prothrombotic propensity [ 3 , 4 ], with elevated coagulation markers [ 5 ]. Therefore, any biomarkers reflecting COVID-19 disease and its severity would necessarily have to be independent of differentially-expressed proteins relating to other conditions; therefore, this proteomic analysis was undertaken in women with and without PCOS to compare with the proteomic biomarkers recently described in COVID-19 using shotgun proteomics followed by parallel reaction monitoring [ 1 ].…”
mentioning
confidence: 99%
“…146 PCOS and 97 control women who presented sequentially to the Department of Endocrinology, Hull and East Yorkshire Hospitals NHS Trust were recruited to the local PCOS biobank (ISRCTN70196169) [ 2 ]. PCOS diagnosis was based on all three Rotterdam consensus diagnostic criteria.…”
mentioning
confidence: 99%
“…As reported previously [ 10 ], cohorts were age-matched, but PCOS women had increased insulin resistance, androgens and CRP (p < 0.001); systolic and diastolic blood pressure, and waist circumference were higher (p < 0.05). As reported, RAS system overactivity was found with elevated renin, and decreased angiotensinogen and ACE2 in PCOS (p < 0.05), indicative of increased hypertensive risk [ 10 ].…”
mentioning
confidence: 73%
“…Polycystic ovary syndrome (PCOS), a cardiometabolic disease encompassing metabolic syndrome, insulin resistance [ 7 ] and obesity with increased T2D risk [ 8 ], also predisposes to severe COVID-19 disease, as suggested by case reports of PCOS women infected by SARS-CoV-2 [ 9 ]. We have reported higher renin and lower angiotensinogen levels, indicating RAS hyperactivation, in PCOS [ 10 ]. Since RAS-related proteins, NRP1 and VEGF, are implicated in COVID-19 severity, we hypothesized that increased risk of severe COVID-19 in PCOS may be reflected in altered soluble NRP1 (sNRP1) levels and their association with RAS-related proteins and VEGF.…”
mentioning
confidence: 99%
See 1 more Smart Citation